Affective responses to electrocutaneous stimulation in three groups of participants with different levels of skin-picking severity - Anne Schienle; Florian Osmani (Cogent Psychology, 2023)
AbstractSome individuals pick their skin excessively which induces skin lesions. These individuals with high severity of skin-picking (SOSP) usually experience their picking not as painful, although this behavior causes physical harm. This may point to lowered pain sensitivity in individuals with elevated SOSP. A total of 144 participants characterized by three different levels of self-reported SOSP received electrocutaneous pulses of different intensities to the skin surface of their left forearm. A mixed-model analysis of variance tested the effects of SOSP group (no/medium/high skin-picking severity) and stimulus intensity (6,16,26,36 mA) on participants’ ratings for perceived intensity/unpleasantness of stimuli and their own affective state (valence, arousal). Relative to participants who never pick their skin, the medium and high SOSP groups reported feeling more unpleasant and aroused during electrocutaneous stimulation. The three SOSP groups did not differ in the evaluation of the stimuli. It has to be noted that only a limited set of stimulation parameters (one location of stimulation; four stimulus intensities) were included. The present findings suggest that emotional responsivity to skin stimulation (but not pain sensitivity) is an important factor in understanding skin-picking behavior.